2013
DOI: 10.1530/eje-12-1106
|View full text |Cite
|
Sign up to set email alerts
|

High penetrance of pheochromocytoma in multiple endocrine neoplasia 2 caused by germ line RET codon 634 mutation in Japanese patients

Abstract: Objective: The precise penetrance of pheochromocytoma (PHEO) in multiple endocrine neoplasia type 2 (MEN2) has not been reported in a large cohort. In this study, we aimed to clarify the codon-specific penetrance of PHEO in MEN2. Design: We established a study group designated the 'MEN Consortium of Japan' in 2008 and asked physicians and surgeons to provide clinical and genetic information on patients they had treated up to 2011. Methods: Data were collected on patients identified as carriers of the RET mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 19 publications
10
50
0
Order By: Relevance
“…PHEO mainly occurs in association with codon 634 and 918 mutations, but rarely in association with codon 618, codon 620 or other mutations (6)(7)(8). A previous study reported that the majority of patients with a codon 634 mutation will develop PHEO and MTC during their lifetime (9), as occurred in the case in the present study. A patient with a codon 634 mutation is prone to develop PHEO and MTC at the same time.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…PHEO mainly occurs in association with codon 634 and 918 mutations, but rarely in association with codon 618, codon 620 or other mutations (6)(7)(8). A previous study reported that the majority of patients with a codon 634 mutation will develop PHEO and MTC during their lifetime (9), as occurred in the case in the present study. A patient with a codon 634 mutation is prone to develop PHEO and MTC at the same time.…”
Section: Discussionsupporting
confidence: 74%
“…The diagnosis of PHEO may be determined prior to MTC (12.9-25.1% of patients), simultaneously with MTC (34.7-38.9% of patients) or following the diagnosis of MTC (40.2-48.2% of patients) (10). In addition, half of all patients with PHEO may be asymptomatic at diagnosis (9,10). However, the patient and son in the present study were diagnosed with labile hypertension, which is the typical manifestation of PHEO.…”
Section: Discussionmentioning
confidence: 57%
“…In a continuous series of 246 RET mutation carriers, Imai et al, described that the age-dependent penetrance of Pheo was 32% by age 50 and 50% by age 76 [9].…”
Section: Discussionmentioning
confidence: 99%
“…In MEN 2A, the onset of Pheo is usually concomitant or subsequent to MTC [10], but in 13-27% of cases it represents the first manifestation of the syndrome [9,11]; moreover it has also been reported a codon specific age-related onset of Pheo [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, pheochromocytoma as a first manifestation of MEN 2A occurs in 9-27% of cases [11,13]. Mutation in codon 634 particularly predisposes to this tumour [11,14]. At the same time, pheochromocytoma related to the mutation in codon 634 is very likely to develop in young age, even in children less than ten years old [15].…”
Section: Discussionmentioning
confidence: 99%